2014
DOI: 10.1177/1099800414558087
|View full text |Cite
|
Sign up to set email alerts
|

Induction of IL-6 by Cytotoxic Chemotherapy Is Associated With Loss of Lean Body and Fat Mass in Tumor-free Female Mice

Abstract: Cancer patients treated with cytotoxic chemotherapy experience fatigue and changes in body composition that can impact physical functioning and quality of life during and after treatment. Interleukin-6 (IL-6) is associated with fatigue in cancer survivors and plays an important role in the regulation of body composition. The purpose of the present study was to determine the specific role of IL-6 in cyclophosphamide-doxorubicin-5-fluorouracil (CAF)-induced changes in fatigue, food intake, and body composition u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
1
18
0
2
Order By: Relevance
“…The chemotherapy drug cisplatin induces muscle atrophy by activating myostatin, IL-6, TNF-/, and IL-1b, which can be prevented by the orexigenic peptide ghrelin in the LLC-induced cachexia model [33]. Cyclophosphamide-, doxorubicin-, and 5-fluorouracil-induced cachexia is associated with increased circulating IL-6, followed by decreased insulin-like growth factor 1 (IGF-1) levels, and can be prevented by germline deletion of IL-6 [34]. Therefore, different chemotherapy agents induce cachexia via distinct mechanisms and further research is needed to understand their transduction pathways.…”
Section: Chemotherapy-induced Cachexiamentioning
confidence: 99%
“…The chemotherapy drug cisplatin induces muscle atrophy by activating myostatin, IL-6, TNF-/, and IL-1b, which can be prevented by the orexigenic peptide ghrelin in the LLC-induced cachexia model [33]. Cyclophosphamide-, doxorubicin-, and 5-fluorouracil-induced cachexia is associated with increased circulating IL-6, followed by decreased insulin-like growth factor 1 (IGF-1) levels, and can be prevented by germline deletion of IL-6 [34]. Therefore, different chemotherapy agents induce cachexia via distinct mechanisms and further research is needed to understand their transduction pathways.…”
Section: Chemotherapy-induced Cachexiamentioning
confidence: 99%
“…Previous study in tumour‐free model has documented a significant muscle loss during doxorubicin treatment, which is apparently unrelated to tumour growth. Given the fact that muscle loss in both humans and animals are closely associated with increased mortality in both cancer patient and elderly, development of other adjuvant intervention to preserve muscle mass, other than Q10 supplementation, should be regarded as a primary goal of cancer patients under doxorubicin therapy.…”
Section: Discussionmentioning
confidence: 96%
“…Doxorubicin has been used extensively for chemotherapy of cancer by the mechanism through which it systemically inhibits cell proliferation in vivo . One of the most devastating symptoms associated with mortality of cancer patients during the chemotherapy is development of sarcopenia . In humans, survival time in patients who were developed sarcopenia was significantly shorter than in patients who were not developed sarcopenia .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Findings from our recent study support this idea. Using a breast cancer chemotherapy treatment model we found that chemotherapy-induced weight loss was significantly greater in wild-type mice than in mice lacking IL-6, even after controlling for food intake and physical activity level (29). EBRT-related fatigue was associated with increased inflammatory gene expression in peripheral tissues and in the circulation.…”
Section: Discussionmentioning
confidence: 99%